2003
DOI: 10.1213/01.ane.0000059225.40049.99
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-3-Glucuronide’s Neuro-Excitatory Effects Are Mediated via Indirect Activation of N-Methyl-d-Aspartic Acid Receptors: Mechanistic Studies in Embryonic Cultured Hippocampal Neurones

Abstract: Large systemic doses of morphine administered to some patients for cancer pain management have been reported to produce myoclonus and allodynia. Indirect evidence implicates the major morphine metabolite, morphine-3-glucuronide (M3G), in these neuro-excitatory side effects. Hence, this study was designed to gain insight into the cellular mechanism responsible for M3G's neuro-excitatory actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…Second, the lower dose of morphine (5.6 mg/kg) produces anxiolytic-like effects at 2 hr post-treatment where the higher dose of 10 mg/kg is without effect, yet plasma levels of M3G at 2 hr post-injection are significantly higher with 10 mg/kg than 5.6 mg/kg of morphine (Barjavel et al, 1995;Zheng et al, 1998). Finally, we are unaware of any reports in the literature of M3G producing anxiolytic-like effects, but there are a number of reports that central administration of this morphine metabolite elicits an excitatory reaction characterized by explosive motor behavior, touch-evoked agitation, myoclonic jerks, and wetdog shakes, behaviors that the rat is most likely to experience as aversive rather than anxiolytic (Bartlett et al, 1994;Hemstapat et al, 2003;Labella et al, 1979;Smith and Smith, 1998). In support of this latter assertion, Bartlett et al (1994) reported that some excitatory effects of M3G are attenuated by pretreatment with an anxiolytic agent (midazolam).…”
mentioning
confidence: 86%
“…Second, the lower dose of morphine (5.6 mg/kg) produces anxiolytic-like effects at 2 hr post-treatment where the higher dose of 10 mg/kg is without effect, yet plasma levels of M3G at 2 hr post-injection are significantly higher with 10 mg/kg than 5.6 mg/kg of morphine (Barjavel et al, 1995;Zheng et al, 1998). Finally, we are unaware of any reports in the literature of M3G producing anxiolytic-like effects, but there are a number of reports that central administration of this morphine metabolite elicits an excitatory reaction characterized by explosive motor behavior, touch-evoked agitation, myoclonic jerks, and wetdog shakes, behaviors that the rat is most likely to experience as aversive rather than anxiolytic (Bartlett et al, 1994;Hemstapat et al, 2003;Labella et al, 1979;Smith and Smith, 1998). In support of this latter assertion, Bartlett et al (1994) reported that some excitatory effects of M3G are attenuated by pretreatment with an anxiolytic agent (midazolam).…”
mentioning
confidence: 86%
“…M3G has been reported to have neuroexcitatory action [10][11][12][13][14][15][16], and this neuroexcitatory action of M3G reduces analgesia of MOR and M6G [17]. Moreover, in cultured hippocampal neurons it was reported that M3G indirectly activates the NMDA receptor resulting in increased cytosol calcium concentrations via a predominantly non-opioidergic mechanism [28,29]. Patients who receive large doses of systemically administered MOR have an elevated plasma concentration of M3G of the main metabolite, which is considered to be the cause of neuroexcitatory actions, such as allodynia or myoclonic jerks.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have explained that in cases where opioid levels are rapidly rising (as in intrathecal administration); opioid metabolites (example morphine-3-glucuronide) cause neuroexcitation and could induce hyperalgesia, as many patients reported increased pain at the sites of ongoing pain [19][20][21].…”
Section: Decreased Reuptake and Enhanced Nociceptive Responsementioning
confidence: 99%